Efficacy of intra-vulvo submucosal prostaglandins on estrous cycles in goats - Bayu Sutaruci Bahari; Herry Agoeshermadi; Faisal Fikri; Trilas Sardjito; Agus Purnomo; Shekhar Chhetri; Salipudin Tasil Maslamama; Muhammad Thohawi Elziyad Purnama (The Indian Veterinary Journal, 2023)
This study aimed to evaluate the efficacy of intra-vulvo submucosal prostaglandins compared to PMSG and hCG on the period of estrous signs and pregnancy rate in goats. A total of 18 goats were assigned to three groups i.e. (T1) injected 4 mg of prostaglandin, (T2) injected 4 mg of prostaglandin followed by a combination of PMSG 200 IU and hCG 100 IU, (T3) injected 4 mg of prostaglandin followed by a combination of PMSG 400 IU and hCG 200 IU. In result, on the time of onset of estrous period, there was no significant difference between the T1, T2 and T3 groups. Meanwhile, the pregnancy rate in goats also showed similar results between the T1, T2 and T3 groups. In conclusion, the intra-vulvo submucosal injection of prostaglandins was reported to have the similar effectiveness as PMSG and hCG to improve the estrous cycle and pregnancy rate in goats.